Bio-inspired blades with local trailing edge flexibility increase the efficiency of vertical axis wind turbines. (November 2022) - Somoano, M.; Huera-Huarte, F.J.
Abstract: This experimental study is focused on quantifying the effect of trailing edge flexibility on the performance of a three straight bladed vertical axis wind turbine, with a chord-to-diameter ratio c / D = 0 . 16 at a moderately high Reynolds number (based on diameter) R e D = 4 ⋅ 1 0 5 . The blades consist of NACA-0015 profiles that are fixed with a pitch angle β = 6 ∘ toe-out, and allow interchangeable trailing edges in the last 17% of their chord length. The research presented here provides a proof of concept for the improved performance of vertical axis wind turbines, due to the effect of flexibility at the trailing edge of their blades. We show that blades with semi-flexible trailing edge, can extend the range of rotor operating regimes, leading to an increase of approximately 10% in the performance of the turbine. An excess of flexibility results in diminished efficiencies.